1990
DOI: 10.1149/1.2086373
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Modeling of Thin Silicon Dioxide Films on Silicon

Abstract: The ellipsometric measurement of refractive indexes for films less than 50 nm thick is of dubious quality due to the significance of the size of random errors relative to the accuracy required to extract reliable index values from the measurements. In this study the various errors are quantitatively assessed as a function of the film thickness, and then compared with experimental data obtained from differently prepared silicon dioxide films on silicon. The new results confirm previous work that shows higher re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…However, the plot clearly establishes the dependence of growth rate on initial clean-up, making this critical for thin oxide films. The date presented on native oxides can be used to reduce the uncertainty using iterative techniques (Kalnitsky et al 1990) and to improve models for this film oxide growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the plot clearly establishes the dependence of growth rate on initial clean-up, making this critical for thin oxide films. The date presented on native oxides can be used to reduce the uncertainty using iterative techniques (Kalnitsky et al 1990) and to improve models for this film oxide growth.…”
Section: Resultsmentioning
confidence: 99%
“…1975, Kalnitsky et al 1990, Kobeda and Irene 1988). These studies have identified the contaminants during hydrofluoric acid (HF) etching (Yang et a/.…”
Section: Introductionmentioning
confidence: 99%
“…We consider the simulated ( and * data sets deduced by Kalnitsky et al 3 for an optical model of the layer Si structure. In this model, the SiO 2 /interface interface transition region between the layer and SiO 2 the Si substrate has been modelled as a graded index layer : the interface layer index varies exponentially n 3 along the interface layer thickness from a value closer to the substrate real index value to the bulk Ðlm SiO 2 index value of 1.46.…”
Section: Simulated Double-layer Data3mentioning
confidence: 99%
“…The ( and * values were generated in the above work3 for di †erent bulk oxide thicknesses with the following parameter values : n 2 (SiO 2 ) \ 1.46, at 6328 0.018 and ' \ 70¡. n 4 (Si Ó) \ 3.858 [ j Kalnitsky et al 3 have subsequently computed the Ðlm index and thickness from these simulated ( SiO 2 and * data by assuming a single-layer model without the interface layer and thus explain the increase in the Ðlm index (Table 1) for thinner Ðlms when the SiO 2 single-layer model is assumed. Some of these simulated ( and * data of the graded index structure with an interface layer thickness of 15 as well as the Ðlm Ó, index and thickness found3 by assuming the single-layer model, are given in Table 1.…”
Section: Simulated Double-layer Data3mentioning
confidence: 99%
“…Also in Figure 2 is shown the calculated spectral dependencies of the refractive index of bulk and thin film SiO 2 calculated using a single term Sellmeier approximation after Jellison'. Since n for thermally grown SiO 2 films is dependent on the thickness 6. ", the use of immersion liquids with different refractive indexes corresponding to the average refractive indexes of the films under investigation renders accuracy improvements possible.…”
Section: Introductionmentioning
confidence: 99%